1977
DOI: 10.1159/000102436
|View full text |Cite
|
Sign up to set email alerts
|

Instrumentation, Working Hypotheses, and Clinical Aspects of Neurostimulation

Abstract: The paper describes instrumentation developed in our laboratory for the therapy of neurological disorders, including (a) hybrid stimulator for chronic use which retains constant current characteristics, providing a low resistance path during the quiescent phase between pulses to minimize the postpulse charge; (b) brain radio stimulators, crystal controlled, with digital logic section and an optoelectric sensor for telemetry of the intensity used; (c) external stimoceiver for experimental and clinical use, comb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1981
1981
2022
2022

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…First, Delgado significantly advanced brain implantation technology by exploring closed‐loop brain stimulation designs and allowing for freedom of movement with long‐term, wireless implantable devices. Namely, Delgado invented the “stimoceiver,” which was a wireless device that used bidirectional radio waves to transmit brain recording data and stimulation pulses between the implanted device and the device used by the physician or researcher 10 (Figure 2). One of his first studies using these devices was his famous bull experiment 9 .…”
Section: Figurementioning
confidence: 99%
“…First, Delgado significantly advanced brain implantation technology by exploring closed‐loop brain stimulation designs and allowing for freedom of movement with long‐term, wireless implantable devices. Namely, Delgado invented the “stimoceiver,” which was a wireless device that used bidirectional radio waves to transmit brain recording data and stimulation pulses between the implanted device and the device used by the physician or researcher 10 (Figure 2). One of his first studies using these devices was his famous bull experiment 9 .…”
Section: Figurementioning
confidence: 99%
“…Work on animals [7], [8] has demonstrated how direct brain stimulation can be used to guide rats through a maze problem, essentially by reinforcement, by evoking stimuli to the cortical whisker areas to suggest the presence of an object, and stimulation of the medial forebrain bundle (thought to be responsible for both the sense of motivation and the sense of reward) when the rat moves accordingly. Early work to translate this research to humans demonstrated radical (and occasionally dubiously interpreted) changes in mood and personalities when such 'pleasure centers' were stimulated [9], [10]. This period saw some seventy patients implanted with permanent micro-stimulators to treat a variety of disorders with reportedly good success, although the indiscriminant use of the procedure and significant failure rate saw it largely condemned.…”
Section: Medical Application Of Implantable Technologymentioning
confidence: 99%
“…Work on animals [4,5] has demonstrated how direct brain stimulation can be used to guide rats through a maze problem, essentially by reinforcement, by evoking stimuli to the cortical whisker areas to suggest the presence of an object, and stimulation of the medial forebrain bundle (thought to be responsible for both the sense of motivation and the sense of reward) when the rat moves accordingly. Early work to translate this research to humans demonstrated radical (and occasionally dubiously interpreted) changes in mood and personalities when such 'pleasure centers' were stimulated [6,7]. This period saw some seventy patients implanted with permanent micro-stimulators to treat a variety of disorders with reportedly good success, although the indiscriminant use of the procedure and significant failure rate saw it largely condemned.…”
Section: Let Implants For Restorative Applicationmentioning
confidence: 99%